2002
DOI: 10.1007/s00213-002-1224-x
|View full text |Cite
|
Sign up to set email alerts
|

The reinstatement model of drug relapse: history, methodology and major findings

Abstract: The data derived from studies using the reinstatement model suggest that the neuronal events that mediate drug-, cue- and stress-induced reinstatement of drug seeking are not identical, that the mechanisms underlying drug-induced reinstatement are to some degree different from those mediating drug discrimination or reward, and that the duration of the withdrawal period following cocaine and heroin self-administration has a profound effect on reinstatement induced by drug cues and stress. Finally, there appears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
1,217
3
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,456 publications
(1,266 citation statements)
references
References 190 publications
30
1,217
3
7
Order By: Relevance
“…Indeed, rimonabant reduced the dopamine-releasing effects of nicotine as assessed by brain microdialysis and drug discrimination. A large body of evidence has shown that dopaminergic transmission plays a role in conditioned responses associated with drugs (Everitt et al, 2001;Shaham et al, 2003). As expected, the D 1 dopamine antagonist SCH23390 (0.01 and 0.03 mg/kg) was found to reduce responding for conditioned cues.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Indeed, rimonabant reduced the dopamine-releasing effects of nicotine as assessed by brain microdialysis and drug discrimination. A large body of evidence has shown that dopaminergic transmission plays a role in conditioned responses associated with drugs (Everitt et al, 2001;Shaham et al, 2003). As expected, the D 1 dopamine antagonist SCH23390 (0.01 and 0.03 mg/kg) was found to reduce responding for conditioned cues.…”
Section: Discussionsupporting
confidence: 66%
“…Factors such as drug-associated environmental stimuli, stress, or drug priming can trigger craving in humans and drug-seeking behavior in laboratory animals (Shaham et al, 2003;Sinha et al, 2000;Weiss et al, 2001;Brody et al, 2002). Cue-induced drug-seeking behavior can be measured in animals using second-order schedules of drug reinforcement or extinction/reinstatement models (Markou et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a clinical study with opioid-dependent patients maintained on naltrexone showed that lofexidine (at twice the daily dose used presently) decreased laboratory measures of stress-and drug cue-induced craving and decreased opioid relapse compared to placebo (Sinha et al, 2007). There is also an extensive preclinical literature showing that lofexidine decreases stress-induced drug-seeking behavior (see Shaham et al, 2003). Given that preclinical studies show that cannabis withdrawal, like opioid withdrawal, is associated with noradrenergic hyperactivity (see Introduction), lofexidine may decrease marijuana relapse in the laboratory by the same mechanism as it decreases opioid relapse: by reducing withdrawal-related noradrenergic hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the same stimuli that reinstate self-administration are capable of inducing the reinstatement of CPP. The most important environmental events that may lead to reinstatement are re-exposure to the drug itself, presentation of drug-associated stimuli or cues and exposure to a stressful event Ribeiro Do Couto et al, 2005a, b;Ribeiro Do Couto et al, 2006; for a review, see Shalev et al, 2002;Shaham et al, 2003;Weiss, 2005).…”
Section: Introductionmentioning
confidence: 99%